PREVALENCE OF NON-ALCOHOLIC FATTY LIVER DISEASE IN REPUBLIC OF BASHKORTOSTAN (REGIONAL RESULTS OF DIREG 2 STUDY) - D. Kh. Kalimullina; A. S. Yurkina; T. I. Ushakova; D. V. Blinov (Фармакоэкономика, 2017)
Non-alcoholic fatty liver disease (NAFLD) is increasingly recognized as an important problem that can lead to cirrhosis and hepatic failure. It may be the most prevalent liver disease. However, knowledge of the epidemiology is limited. These findings encourage to conduct a larger sample size study to evaluate the real prevalence of NAFLD in the Russian population. It is important to know current prevalence of NAFLD. DIREG 2 study was performed under umbrella of leading Russian professional societies in partnership with Sanofi Russia.Objective: to estimate the prevalence of NAFLD within the general practitioners and gastroenterologist’s patient flow. It is important to know current prevalence of NAFLD in Republic of Bashkortostan and to compare with DIREG 2 results.Materials and methods. Epidemiologic, observational, multicenter study assessing the prevalence of NAFLD among patient’s outpatient practice. A total of 50145 patients (3232 in Republic of Bashkortostan) including those suspected of having NAFLD criteria were enrolled in the Program. The investigators were qualified doctors (GPs/therapist’s/gastroenterologists), providing outpatient care for the population. The epidemiological data were obtained, recorded during two routine patient visits to investigating centers.Results. Percentage of patients with revealed NAFLD within the patient flow primary or consistently coming to selected doctors for any reason including those suspected of having NAFLD was 37,3% in Russia vs 40,8% in Republic of Bashkortostan.Conclusion. Prevalence of NAFLD among patient flow of doctors in Russia is quite high. It has been revealed a high prevalence of NANCFLD within the patient flow primary or consistently coming to selected by doctors for any reason.